Probability and statistical inference in ancient and medieval Jewish literature - Rabinovitch, Nachum L., 1928-2020 (Heritage., 1973)
This book throws new light on the origins of probability and statistics. Heretofore these were thought to be entirely the creation of recent centuries, but it is demonstrated here that probability has a much longer history, reaching back to biblical times.